Home range size scales to habitat amount and increasing fragmentation in a mobile woodland specialist. Issue 24 (18th November 2019) - Gardiner, Riana; Proft, Kirstin; Comte, Sebastien; Jones, Menna; Johnson, Chris N.
Abstract: Studies of impacts of fragmentation have focused heavily on measures of species presence or absence in fragments, or species richness in relation to fragmentation, but have often not considered the effects of fragmentation on ranging behavior of individual species. Effective management will benefit from knowledge of the effects of fragmentation on space use by species. We investigated how a woodland specialist, the eastern bettong ( Bettongia gaimardi ), responded to fragmentation in an agricultural landscape, the Midlands region of Tasmania, Australia. We tested whether individual bettongs could adjust home range size to maintain access to essential habitat across three sites differing in degree of fragmentation. We used GPS tracking to measure the home ranges of individual bettongs. Our models tested the effects of habitat aggregation and habitat amount measured at two radii comparable to a typical core range (250 m) and a typical home range (750 m), and habitat quality and sex on individual home range. We also tested the relationship between fragmentation on woodland used to determine whether individuals could compensate for fragmentation. Depending on the spatial scale of fragmentation measured, bettongs altered their movement to meet their habitat requirements. Our top model suggested that at the core range scale, individuals had smaller ranges when habitat is more aggregated. The second model showed support for habitat amount at the core range, suggesting individuals can occupy larger areas when there is a higher amount of habitat, regardless of configuration. Species that are relatively mobile may be able to compensate for the effects of habitat fragmentation by altering their movement. We highlight that any patch size is of value within a home range and management efforts should focus on maintaining sufficient habitat especially at the core range scale. Abstract : For a mobile species that can cross gaps, the configuration of patches does not hinder movement given there is sufficient habitat.